2019
DOI: 10.1038/s41598-019-44958-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential activity of the antioxidant defence system and alterations in the accumulation of osmolyte and reactive oxygen species under drought stress and recovery in rice (Oryza sativa L.) tillering

Abstract: The objective of this study was to investigate the effects of drought stress on the activity of antioxidant enzymes and osmotic adjustment substance content in the tillering period of drought-sensitive and drought-tolerant rice cultivars. The results showed that the superoxide dismutase (SOD), peroxidase (POD), catalase activity (CAT), hydrogen peroxide content, soluble protein content and soluble sugar content increased with the accumulation of time and intensity of drought stress. Compared with the drought-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
57
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 26 publications
(25 reference statements)
6
57
0
2
Order By: Relevance
“…Our results also showed that ascorbate-glutathione cycle (ASA-GSH) played an important role on scavenging the over production of H 2 O 2 due to osmotic stress in Chinese potato genotypes. APX, GR, MDAR and DHAR involved in ASA-GSH cycle were also higher in stressed plants than that in control 39,41 . This series of enzymatic and non-enzymatic antioxidants such as SOD, CAT, GPX and DHAR delays leaf senescence induced by PEG stress 42 .…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Our results also showed that ascorbate-glutathione cycle (ASA-GSH) played an important role on scavenging the over production of H 2 O 2 due to osmotic stress in Chinese potato genotypes. APX, GR, MDAR and DHAR involved in ASA-GSH cycle were also higher in stressed plants than that in control 39,41 . This series of enzymatic and non-enzymatic antioxidants such as SOD, CAT, GPX and DHAR delays leaf senescence induced by PEG stress 42 .…”
Section: Discussionmentioning
confidence: 80%
“…Khanna-Chopra and Selote 38 reported a higher level of antioxidative machineries in stressed plants over non-stressed plants. Similarly, Wang et al 39 reported that the osmotic adjustment ability in tolerant cultivar is more efficient over susceptible ones. SOD is the first line of antioxidant which rapidly scavenges O 2 and restricts the production of OH 40 .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…SOD, CAT, and POD are reportedly the most important enzymes involved in the removal of reactive oxygen species (ROS) (Hosseini et al, 2018). The increased activities of SOD and CAT in the PP-inoculated and FA-inoculated plants, and the increase of soluble protein content in the AV-inoculated and PP-inoculated plants at water stress indicated that the antioxidant enzyme activity and soluble protein level were enhanced to remove ROS under drought stress conditions (Hosseini et al, 2018; Wang et al, 2019). Using soluble proteins as compatible osmolytes can facilitate osmotic adjustment, leading to an increased tolerance to dehydration (Doganlar et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies carried out by Sakamoto and Murata (2000) and Saxena et al (2019) indicated that osmoprotectant substances, such as glycine betaine, play an essential role in cell stabilization by balancing the structure of the protein quaternary and membrane structure against the adverse effects of salinity. Besides, it facilitates osmotic adjustment by lowering the internal osmotic potential, which contributes to the ability to tolerate water pressure, stabilizing the PSII and RuBisCO complexes in the process of photosynthesis under seizure conditions (Holmström et al 2000;Wang et al 2019;Huang et al 2020). The positive effects and exogenous application of glycine in plants grown under salinity stress conditions have been shown to protect plant cells (Demiral and Türkan 2004;Saxena et al 2019).…”
Section: Introductionmentioning
confidence: 99%